A Case Report Of A Lady With Right-Sided Asymptomatic Diaphragmatic Paralysis With Cervical Spine C4/C5 Anterolisthesis - Ng, CS; Soo, CI; Ban, AYL; Faisal, AH; Aziz, AM; Ummi, ND; Hassan, T; Roslina, AM (Wiley-Blackwell, 2024)
Indexed by WOS